Numerical-hydrodynamic analysis, vickers hardness, and tensile test of cast-brass alloy for boat propellers - Akhyar Akhyar; Iqbal Iqbal; Muhammad Bahi; Ahmad Farhan; Seab Piseth (Jurnal POLIMESIN, 2023)
Computational Fluid Dynamics (CFD) has been applied to simulate boat propellers. The material for boat propellers generally uses a brass alloy metal which is produced by a casting process. The purpose of this study was to simulate CFC propellers, evaluate the hardness and tensile strength of samples cast from the brass alloy used to produce ship propellers. The methods show that turbulent kinetic energy, density streamline characteristic, and velocity distribution are simulated boat propellers with CFD applications. Furthermore, the propeller is cast to observe the surface hardness and tensile strength of the cast alloy. The results revealed that the boundary conditions - which served as the simulation's input parameters, the geometry of the rotating and stationary domains, the geometry and type and number of gratings, the geometric accuracy of the propeller model, mass flow rate, rotational angular velocity, and stationary angular velocity - all had a significant impact on the parameters. Brass alloy and cast alloy raw material hardness values were measured on the surface of the propeller casting product. While 128 HV was attained after casting, the average hardness value for solid cylinders manufactured of the raw metal alloy was 171.67 HV. The three test sessions' stress vs. strain graphs were produced using the Cu-Zn alloy metal's tensile test results. The cast Cu-Zn alloy has a maximum tensile strength of 352 MPa and a maximum yield stress of 330 MPa.